Colorimetric and biometric characterization of broad bean seeds (Research, Society and Development, 2023)
Differences found in the physical and morphological parameters of seeds may indicate the prevalence of genetic variability among populations of cultivated species. In addition, they are essential parameters for manufacturing machinery and equipment that can act in the production, processing, and storage of grains for marketing purposes. This research aimed to evaluate the colorimetric and biometric aspects of bean seeds (Phaseolus lunatus L.) for their characterization and distinction. The colorimetric characterization was performed through the parameters: Hue angle, value, and chroma; and biometric: utilizing length; of width; thickness; seed volume index; geometric, equivalent, and arithmetic mean diameter; surface area; volume; the circularity and sphericity of bean seeds from the state of Ceará. We analyzed 100 seeds of 17 bean genotypes, divided into five replicates of 20 seeds for each genotype, using analysis of variance, the Tukey test, linear correlation, analysis by principal components, and analysis of hierarchical grouping. The predominant colorations of the genotypes were white and light gray, while dark red and light-gray -yellow were the minority. All biometric parameters analyzed showed significant statistical differences, which suggests a degree of dissimilarity in their linear dimensions. It is concluded that there is genetic variability in the colorimetric and biometric characteristics of bean seeds grown in Ceará.